The teacher mentoring role and the reflexive teacher formation during supervised internships in the science education area - Altarugio, Maisa Helena (2019)
In the initial teacher education scenario, the supervised internships are considered as privileged spaces for the teacher’s professional development, while a reflexive practice is one of the paradigms which guide this formation. Hence, a significant part of the formation of a future professional lies on the university professor who takes the responsibility for the orientation of these practices. In this context, this study has the objective to identify and analyze how professors at the beginning of their career paths, who have just taken the role of supervising the practices, conceive and deal with their mentoring role and with the function of orienting reflexive practices in the education of trainee teachers. Eight professors from different teacher training courses in the Science Education area at a public federal university in Brazil have participated in this case study, where semi-structured interviews and content analysis were used as the main techniques. The results have suggested that, for one group of these professors, the reflection would have a transformative and critical function over their practices and their professional contexts. On the other hand, for the other group, the teacher mentoring role seemed to present a more pragmatic preoccupation, as well as the function and the way to conduct this reflection. While they are moving towards accomplishing their role as teacher mentors, other factors also show some influence in building their identities. Regarding the field of teacher education and the professionalization of education, this study has pointed out to some paths towards which it is possible and necessary to advance and it may contribute to leave teaching from a critical and reflexive orientation as a heritage for the next generations.